IMPORTANCE OF SYSTEMATIC FERTILIZATION WITH MINERAL AND ORGANIC FERTILIZERS FOR PRESERVING AND INCREASING SOIL FERTILITY - Violeta Maria SIMIONESCU; Marioara RUSU; Ion BULICA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present paper makes an analysis of the results obtained on the long-term experience with chemical and organic fertilizers with regard to the chemical condition of soils (pH, total nitrogen content, soluble phosphorous and humus). After thirty years of experiments, we like to make known the importance of systematic fertilizer application for preserving and/or increasing soil fertility, as sustainable development measure. Through long-term experiments with chemical and organic fertilizers, located in representative pedo-climatic area of Romania, important information werefound. They covered crop fertilization with adequate fertilizer application rates for obtaining maximum and economically optimum yields, the best use of nutrients and gaining high quality harvests; at the same time, important information could be acquired on the complex interactions between crops x soil x weather, necessary data for conserving and/or increasing soil fertility and for environment protection. The use of nitrogen and phosphorous fertilizers, on large scale, in Romania determined us to investigate the results under the fertilization variants with these macro-elements. At the same time, we also took into consideration the results on the evolution of the soil chemical condition through the application of organic fertilizers (manure) every four years. The pH level in the variants chemically fertilized with nitrogen and/or phosphorous decreased.